The Prisoners Review Board of Western Australia: What do the Public Know about Parole?. Issue 3 (1st March 2017) - Gately, Natalie; Ferguson, Catherine; Ellis, Suzanne; Cock, Robert
Abstract: Previous international research has indicated that the public hold incorrect perceptions of the criminal justice system and have little understanding of how it operates. This can result in a lack of confidence in the system, often stemming from a lack of knowledge and media presentation of crime stories. The present study utilised qualitative methodology to gain an in-depth understanding of the public knowledge about parole. Semi-structured interviews were conducted with 38 West Australians aged between 18–63 years. Cultivation theory was used to conceptualise how particular media events at the time permeated participants' explanations of parole. This research contributes to understanding the public perception of the parole system in Western Australia and provides recommendations to enhance public knowledge of the parole system.